Assessment of the private health sector in the Republic of Congo - Makinen, William Martin (Investment climate in health series., 2012)
This country assessment is part of a set of studies planned in order to provide a better understanding of how to improve the business environment in which the private sector operates in Congo and other African countries. The assessment was conducted in order to establish a baseline of information, to help with political decision-making and provide market information. The private health sector assessment in the Republic of Congo provides a diagnosis of the nature and the effectiveness of the interface between the public and private sectors, establishes a dialogue on policy with stakeholders, and makes recommendations for reform that would bolster public and private involvement. The methodology is based on a supply and demand approach to identify market, policy and institutional barriers, and options for reducing these barriers by changing policies and initiatives. The information pertaining to demand reveals how users perceive private providers and their potential. The information pertaining to supply gives a better understanding of the role that private providers play and the challenges they encounter. The institutional information shows how Congo's institutions have facilitated or hampered the private participation. The study methodology includes the following aspects: (i) presentation of the general context of the private health sector in Congo, (ii) multidimensional analysis of demand, (iii) multidimensional analysis of supply, and (iv) analysis of institutional context. Options for action presented in this report include (i) policy and governance initiatives, (ii) regulatory initiatives, (iii) incentive initiatives, and (iv) concrete measures for public-private partnerships (PPP) in the health sector.